Influencing factors on green innovation efficiency of Specialized, Refined, Peculiar, and Innovative enterprises - Chen, Yiting; Fu, Ersheng; Yu, Yaguai; Yu, Zhuoyan; Li, Xiyi (The Economics and Finance Letters, 2025)
Evaluation index system of green innovation input-output of Specialized, Refined, Peculiar, and Innovative (SRPI) enterprises is constructed to assess how internal factors affect green innovation efficiency, using Ningbo as the research object. Based on the data of SRPI enterprises in Ningbo from 2017 to 2022, green innovation efficiency of SRPI enterprises is evaluated by DEA model, with input-output index selected across green and innovation dimensions. The Systematic Generalized Method of Moments (GMM) Dynamic model is applied to evaluate how internal variables enhance eco-innovation effectiveness. First, comprehensive technical efficiency, pure technical efficiency, and scale efficiency of SRPI enterprises in Ningbo are not optimized, with variations observed in green innovation efficiency across different city regions; second, internal factors, including market credit, internal capital allocation, financial stability, and risk resilience, contribute positively to enhancing the efficiency of green innovation; and last, cash flow, inventory, and supply chain management constrain the enhancement of green innovation outcomes. Countermeasures are proposed, including improving internal management, increasing technology research and development, and strengthening risk management. The research is conducive to facilitating sustainable industrial transformation, advancing Ningbo’s manufacturing sector into more sophisticated, intelligent, and eco-efficient operational models.